Analysis of the Comparison Between Residents’ Perception and Field Measurement of Visual and Thermal Comfort (Case Study: Student Dormitory Building) - Yulianto, Dwi; Irawati, Inggar Septhia; Nugroho, Arief Setiawan Budi (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2024)
As public buildings, student dormitories must be comfortable as they host most of the students’ lives and activities. A space’s visual and thermal comfort significantly impacts the occupants’ activities and productivity. Indicators for assessing the building comfort level include visual, thermal, and noise comfort in spaces or buildings. This paper presents the results study of the building’s visual and thermal comfort measurement and the occupants’ perception toward comfort. This paper also presents the comparison between that measurement and the occupants’ perceptions. This research employs a mixed-methods approach consisting of qualitative methods (occupants’ perception questionnaire) and quantitative methods (field measurements of lighting levels, air temperature, and humidity). Data were collected through questionnaires distributed to dormitory residents and field measurements using an Environmental Meter 4 in 1 to measure natural and artificial lighting levels, air temperature, and humidity. The data obtained were analyzed and then presented in a descriptive format. Based on residents’ perceptions, the findings indicate that the overall visual and thermal comfort in the dormitory building falls within a good category. The field measurements on natural lighting, air temperature, and humidity show that the student dormitory building meets the established comfort standards. However, the artificial lighting of staircases and corridors doesn’t meet the standards due to many non-functioning lights and low lumen levels. Overall, the lighting, temperature, and humidity conditions in the dormitory building are influenced by building design, orientation, surrounding environment, and occupants’ behavior. To enhance comfort and health for residents, improvements in artificial lighting systems, enhancement of natural ventilation, and education on the importance of good air circulation are necessary.